Survei Hasil Belajar Pendidikan Jasmani Olahraga dan Kesehatan Melalui E-Learning Siswa Smk Negeri Kota Sukabumi - Bachtiar Bachtiar; Asri Puspita Putri; Firman Maulana (Universitas PGRI Semarang, 2021)
Based on the results of respondents through the google form, the researcher can conclude that students feel that learning physical education, sports and health through e-learning or online learning is not effective. In this study, the writer has the objective to find out the Physical and Physical Education Learning Outcomes through E-Learning of State Vocational School Students in Sukabumi City in 2019/2020 Academic Year in the form of survey research with descriptive presentation methods. Based on the results of data analysis, descriptive analysis, research results testing and discussion, it can be concluded that the learning outcomes of physical and health physical education through e-learning of State Vocational School students in Sukabumi City 2019/2020 Academic Year are in the